2017
DOI: 10.1121/1.4979055
|View full text |Cite
|
Sign up to set email alerts
|

Auditory salience using natural soundscapes

Abstract: Salience describes the phenomenon by which an object stands out from a scene. While its underlying processes are extensively studied in vision, mechanisms of auditory salience remain largely unknown. Previous studies have used well-controlled auditory scenes to shed light on some of the acoustic attributes that drive the salience of sound events. Unfortunately, the use of constrained stimuli in addition to a lack of well-established benchmarks of salience judgments hampers the development of comprehensive theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(119 citation statements)
references
References 38 publications
(52 reference statements)
10
99
4
Order By: Relevance
“…The link between roughness and subjective salience is in line with previous reports (e.g. Arnal et al, 2015;Huang and Elhilali, 2017;Sato et al, 2007) (Itti and Koch, 2001). We found that none of the parameters derived from that model correlated with the present crowd-sourced scale.…”
Section: Crowd-sourced Saliencesupporting
confidence: 92%
See 2 more Smart Citations
“…The link between roughness and subjective salience is in line with previous reports (e.g. Arnal et al, 2015;Huang and Elhilali, 2017;Sato et al, 2007) (Itti and Koch, 2001). We found that none of the parameters derived from that model correlated with the present crowd-sourced scale.…”
Section: Crowd-sourced Saliencesupporting
confidence: 92%
“…We found that, despite the fact that loudness is known to be a prominent contributor to perceptual salience (Huang and Elhilali, 2017;Kayser et al, 2005;Liao et al, 2016), subjective salience in the present set did not correlate with loudness (p=0.076; see Methods for details about the loudness measure). This may be partly because level was RMSnormalised thus removing some of the larger differences in loudness between sounds.…”
Section: Salience Ratingcontrasting
confidence: 58%
See 1 more Smart Citation
“…Transients (onsets of individual tones) in regular streams are predictable and thus do not require substantial processing resources, making it easier to ignore regular patterns when these are task irrelevant (Andreou et al, 2011;Southwell et al, 2017). On the other hand, unexpected events in an otherwise predictable stream are rendered as 'surprising' or 'salient' and capture bottom-up attention (Kaya & Elhilal, 2014;Huang & Elhilali, 2017;Southwell & Chait, 2018).…”
Section: Sensitivity To Regularity In the Service Of Auditory Scene Amentioning
confidence: 99%
“…is still an open question as to whether the selectivity we observe here is a result of "bottom-up" 447 processing, due to auditory processing that does not require subject engagement, or "top-down" 448 19 factors that depend upon the subject's cognitive state. Disambiguating these two is tricky 449 because specific stimuli with particular acoustic characteristics such as sparsity and roughness 450 could engage a subject's attention (Huang and Elhilali, 2017;Zhao et al, 2019). However, we 451 think it is unlikely that subjects were actively attending to speech and music more than other 452 sounds in the stimulus set because the behavioral task places no special emphasis on these 453 stimuli and all stimuli likely became less interesting over many repeats (>80 presentations).…”
mentioning
confidence: 99%